Peran Kelekatan (Attechment) antara Guru dan Peserta Didik dalam Proses Pembelajaran di Sekolah Dasar - Ikhwan Sunaryo; Ichsan (Yayasan Al-Afif, 2025)
This article discusses the emotional gap between teachers and students in elementary school, which often affects the effectiveness of the learning process. This library research aims to analyze the role of attachment between teachers and students in supporting learning motivation and students' socio-emotional development. The results show that secure attachment creates a positive learning environment, increases student self-confidence, and supports active engagement and healthy emotional regulation. Students with strong relationships with teachers tend to be more independent and emotionally resilient. Thus, teacher-student attachment is a fundamental element in meaningful and holistic learning experiences in elementary education